Measurement system of starch particles using digital images - Reséndiz, Juan Carlos de Jesús; Hernández Zavala, Antonio; Méndez Montealvo, Ma. Guadalupe del Carmen; González Barbosa, José Joel; Fonseca Florido, Heidi Andrea; Gómez Aldapa, Carlos Alberto (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
This paper introduces a vision system capable of identifying and measuring achira starch particles. It focuses on identifying the particle and calculating the area of each particle when they are exposed to different temperatures. This tool serves to characterize starch types which are not well known but are available as economic alternative sources. The system is composed of three stages: the image segmentation algorithms implemented in MATLAB software using morphological transformation operators, the Watershed technique of controlled markers segmentation, and the properties calculation out of the binarized and segmented image. As results, we have a clear segmentation where the efficient particle count and the correct identification of the area of each particle is observed. Nevertheless, the project did not reach all the expect due to the extended particles lost the maltese cross.